Alfalfa: its place among Kansas crops - Smith, Edwin Lee (My University, 1898)
Introduction: Kansas is preeminently an agricultural state. Its soil is rich in the natural elements, and ever ready to write with the efforts of the farmer to make mother earth yield bountifully from her great natural storehouse. The farmer plows and sows, the rains descend, and the seed sprouts. He looks out over his beautiful broad fields and smiles on his prospects for a plentiful harvest. What is there that the Kansas Farmer could not raise on his rectangular fields had he the showers when needed? The population of Kansas is made up of an agricultural people. They have come from all parts of the world; bringing with them their ideas of husbandry. They came here in the early days of the state, when the buffalo roamed over the plains, and have since battled against poverty, hard-times, and Kansas grass-hoppers.
Citation: Smith, Edwin Lee. Alfalfa: its place among Kansas crops. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Agriculture; Farmers; Alfalfa; Kansas; Theses; Manuscripts (documents)